2019
DOI: 10.1515/jpem-2018-0441
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the diagnosis of insulin autoimmune syndrome (Hirata’s disease) in a hypoglycemic child: a case report and review of the literature

Abstract: Background Insulin autoimmune syndrome (IAS) is a rare cause of hyperinsulinemic hypoglycemia (HH) not addressed as a potential differential diagnosis in current pediatric guidelines. We present a case of IAS in a child with no previous history of autoimmune disease, no previous intake of triggering medications and absence of genetic predisposition. Case presentation A 6-year-old boy presented with recurrent HH (blood glucose of 26 mg/dL [1.4 mmol/L] and insulin of 686 μU/mL). Abdominal imaging was normal. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Hirata’s disease has also been reported as the cause of transient hypoglycemia in children, who could have lower levels of blood insulin than in older patients, making this disorder as an important pitfall in the differential diagnosis of childhood HH.…”
Section: Discussionmentioning
confidence: 99%
“…Hirata’s disease has also been reported as the cause of transient hypoglycemia in children, who could have lower levels of blood insulin than in older patients, making this disorder as an important pitfall in the differential diagnosis of childhood HH.…”
Section: Discussionmentioning
confidence: 99%
“…This is generally due to the body's stress response and increased muscle activity, rather than directly affecting the musculoskeletal organs. Over time, severe and frequent hypoglycemia can have various detrimental effects on the body; however, specific musculoskeletal damage is not commonly reported [10]. This case report showed that controlling serum blood glucose levels can alleviate systemic joint pain; therefore, higher and lower glucose levels can affect joint pain.…”
Section: Discussionmentioning
confidence: 80%
“…Our patient was only recommended to eat small and frequent meals low in carbohydrates. This is effective because postprandial hyperglycemia is reduced and consequently, the insulin release [ 18 ].…”
Section: Discussionmentioning
confidence: 99%